The Effect Of Return On Equity (ROE) On Company Value - Dewi, Astriana; St. Nurhayati; Andi Faisal (Islamic Financial And Accounting Review, 2023)
: The purpose of this study is to find out how good the level of return on equity (ROE) is on the value of companies in the Jakarta Islamic Index (JII) group in 2019-2021, to find out how good the value of companies listed in the Jakarta Islamic Index (JII) group in 2019-2021, to find out the relationship of return on equity to company value after the effect of return on equity to the value of companies in the Jakarta Islamic Index group for 2019-2021. The results obtained from this study in testing the analysis of data requirements are normally disbusted with sig values. 0.200 > 0.05 then the data can be said to be normally distributed and the results of this analysis can be continued for the next regression analysis and correlation testing with a sig of 0.000 < 0.05 which means that there is a relationship between the decline on equity to the value of the company in the Jakarta Islamic Index group and the results of the nonparametric correlation test there is also a significant relationship between the two variables, namely the return on equity variable (ROE) is the value of the company, and the partial test (T) shows that the sig t result is greater than 0.05, which is 0.000 < 0.05 and the coefficient of determination test of 0.729 which means that 72.9% of the company's value can be explained by the return on equity because it is in the high category while 27.1% is explained by other variables outside the variables studied. So it can be said that there is a positive and significant influence on equity on the value of companies in the Jakarta Islamic Index (JII) group.